Evaluación y caracterización de ácidos orgánicos presentes en la bebida fermentada ancestral de chonta (Bactris gasipaes) con kéfir. - Taipe Toapanta, Carlos Javier (2021)
Ancestral beverages are part of the culture and customs of indigenous peoples, including chonta chicha, which is a traditional fermented beverage from the Amazonian provinces of Ecuador, made mainly from chontaduro, characterized by its high content of carbohydrates, fats, minerals, and carotenoids. The main objective of this research was the evaluation and characterization of organic acids present in the ancestral fermented beverage of chonta with kefir. For the elaboration of this beverage, the result of the experimental design of eight treatments of yeast and kefir in the research work carried out at the Technical University of Cotopaxi in 2019 entitled: "Evaluation of the fermentation of chonta (Bactris gasipaes) employing kefir fermenting microorganisms and yeast to obtain a fermented beverage"; for the present research the T4 sample was replicated as the best treatment a1b4 (kefir 20%) due to its physical-chemical characteristics evaluated and discarding yeast as a fermentative agent. The results obtained from the physical-chemical analyses were similar to the results of the research underlying the current work on the fermentation process of chonta masate. In the physical-chemical analysis of the ancestral fermented drink of pasteurized chonta, the following was obtained: 4.9 pH; 0.029 % acidity; 2.9 brix degrees and 0.29 alcoholic degrees. For the analysis of organic acids, the high performance liquid chromatography (HPLC) method chosen by the National Institute of Agricultural Research Santa Catalina Experimental Station at the Food Analysis and Research Service Laboratory. was used. Two samples (M1 and M2) of the T4 treatment were analyzed. The detection and quantification of acids (lactic, malic, tartaric and succinic) was carried out by comparing the retention times of the standards and the samples. Malic acid presented the highest concentration in sample M1 with 96.3 mg/100 ml, lactic acid in concentrations of 70.83 mg/100 ml, and tartaric acid in concentrations of 39.19 mg/100 ml. In sample M2 the concentration of malic acid is 103.17 mg/100 ml, lactic acid in concentrations of 67.26 mg/100 ml, tartaric acid in concentrations of 40.00 mg/100 ml. The presence of succinic acid was not detected in either sample. The presence and concentrations of organic acids depend on the influence of factors such as the maturity and variety of the fruit, the quality of the ferment used and the environment where the fermentation process takes place. The organic acids confer sensory characteristics to the ancestral fermented chonta beverage, malic acid gives it a sensation of freshness, lactic acid causes a mild acid sensation and stability, while tartaric acid generates an astringent flavor.